Increased Central and Peripheral Thyroid Resistance Indices During the First Half of Gestation Were Associated With Lowered Risk of Gestational Diabetes—Analyses Based on Huizhou Birth Cohort in South China - Liu, Zhao-min; Li, Guoyi; Wu, Yi; Zhang, Di; Zhang, Sujuan; Hao, Yuan-Tao; Chen, Weiqing; Huang, Qi; Li, Shuyi; Xie, Yaojie; Ye, Mingtong; He, Chun; et al. (Frontiers in Endocrinology, 2022)
Objectives The study aims to explore the relationship of thyroid function and resistance indices with subsequent risk of gestational diabetes (GDM). Design This was a longitudinal study embedded in the Huizhou Birth Cohort. Methods Total 2927 women of singleton pregnancy were recruited from January to October of 2019. Thyroid central resistance indices were evaluated by Thyroid Feedback Quartile-based index (TFQI), Thyrotrophy T4 resistance index (TT4RI) and TSH index (TSHI) based on plasma free thyroxine (FT4) and thyroid stimulating hormone (TSH) levels during the first half of pregnancy. Thyroid peripheral sensitivity was assessed by free triiodothyronine (FT3) to FT4 ratio (FT3/FT4), a proxy of deiodinase activity. GDM was diagnosed between 24 to 28 weeks of gestation by a standardized 75g oral glucose tolerance test. Multivariable linear and logistic regression was applied to examine the associations of thyroid markers with GDM risk. Results FT3 and FT3/FT4 were positively associated with both fasting and post-load glucose levels, while TSH, TSHI, TT4RI and TFQI were negatively associated with 1 and 2 hrs post-load glucose levels. Compared with the lowest quartile, GDM risk in the highest quartile increased by 44% (OR=1.44，95%CI：1.08-1.92, Ptrend=0.027) for FT3, and 81% (OR=1.81，95%CI: 1.33-2.46, Ptrend<0.001) for FT3/FT4, while lowered by 37% (OR=0.63, 95%CI: 0.47-0.86, Ptrend=0.002) for TSHI, 28% for TT4RI (OR=0.72，95%CI：0.54-0.97, Ptrend=0.06) and 37% for TFQI (OR=0.63, 95%CI：0.46-0.85, Ptrend<0.001). Conclusions This longitudinal study indicated that higher FT3 and FT3/FT4, while lower central thyroid resistance indices were associated with increased risk of GDM.